Differentiated Instruction in Indonesian Private Kindergartens: Challenges in Implementing an Independent Curriculum - Ika Maryani; Suyatno Suyatno; Ristiyati Ristiyati (International Journal of Educational Management and Innovation, 2023)
Differentiated instruction facilitates learning based on students’ unique interests, preparedness for learning, and learning profiles. Many teachers lack a comprehensive understanding of differentiated instruction, particularly in kindergarten. Teachers used to employ Student Worksheets to facilitate learning. This study aims to: (1) the implementation of differentiated instruction at an Indonesian private kindergarten, (2) the factors that facilitate the instruction’s implementation, and (3) the efforts to deal with any challenges encountered during the implementation of the instruction. This study employed a qualitative case study design to capture a phenomenon comprehensively and contextually by gathering data directly from the subject under investigation. The study was executed at Aisyiyah Kindergarten, Sukorejo, Indonesia. It is the only Indonesian kindergarten in Sukorejo that incorporates an independent curriculum called Sekolah Penggerak. Teachers implement holistic-integrative learning design to differentiate instructional activities. Learning media containing STEAM Loose parts were utilized to determine various factors that may facilitate or impede the instruction. Factors that facilitate instruction include the learning environment, media utilization, teachers’ creativity, the student-teacher relationship, the implementation of teaching techniques, students’ psychological well-being, and community support beyond the school setting. The inhibitory factors encompass a scarcity of learning resources, students’ lack of preparedness for learning, a shortage of teachers, and inadequate infrastructure. This study revealed that the school tried to address the challenges by collaborating with the community inside and outside the school, such as with student guardians, the foundation administrator, and related agencies